Intelligent leadership what you need to know to unlock your full potential - Mattone, John (AMACOM, 2013)
In today's business environment, leaders at all levels are facing enormous challenges when it comes to achieving and sustaining breakthrough operating results. Globalization, economic change, more stringent regulation, and tougher governance make realizing shareholder value increasingly difficult. "Intelligent Leadership" is written for leaders who want to become more effective, strategic, operationally focused, and balanced. It is for leaders who are striving to take control of their destiny and become the best they can be. In this groundbreaking book, leadership coach John Mattone-recently named to the "guru radar" by the prestigious Thinkers50-taps into his years of experience working with high-achieving professionals to give readers a roadmap for developing and mastering their executive maturity. Supplying three unique tools - the Wheel of Leadership Success, Map of Leadership Maturity, and the Leadership Enneagram - the book helps readers calibrate their abilities so they can simultaneously focus on their strengths and address their weaknesses. The goal is to improve key tactical competencies (such as critical and strategic thinking, decision-making, talent and team leadership, and communication) and integrate them with equally important inner traits like values, character, and beliefs in order to achieve their leadership potential. Features best practices, authoritative research, practical assessments, and enlightening examples of both good and bad leadership, this book equips readers with the knowledge, skills, and passion they need to become the leaders they were meant to be.